Imaging temozolomide-induced changes in the myeloid glioma microenvironment - Foray, Claudia (Theranostics, 2021)
Rationale: The heterogeneous nature of gliomas makes the development and application of novel treatments challenging. In particular, infiltrating myeloid cells play a role in tumor progression and therapy resistance. Hence, a detailed understanding of the dynamic interplay of tumor cells and immune cells in vivo is necessary. To investigate the complex interaction between tumor progression and therapy-induced changes in the myeloid immune component of the tumor microenvironment, we used a combination of [(18)F]FET (amino acid metabolism) and [(18)F]DPA-714 (TSPO, GAMMs, tumor cells, astrocytes, endothelial cells) PET/MRI together with immune-phenotyping. The aim of the study was to monitor temozolomide (TMZ) treatment response and therapy-induced changes in the inflammatory tumor microenvironment (TME). Methods: Eighteen NMRI(nu/nu) mice orthotopically implanted with Gli36dEGFR cells underwent MRI and PET/CT scans before and after treatment with TMZ or DMSO (vehicle). Tumor-to-background (striatum) uptake ratios were calculated and areas of unique tracer uptake (FET vs. DPA) were determined using an atlas-based volumetric approach. Results: TMZ therapy significantly modified the spatial distribution and uptake of both tracers. [(18)F]FET uptake was significantly reduced after therapy (-53 ± 84%) accompanied by a significant decrease of tumor volume (-17 ± 6%). In contrast, a significant increase (61 ± 33%) of [(18)F]DPA-714 uptake was detected by TSPO imaging in specific areas of the tumor. Immunohistochemistry (IHC) validated the reduction in tumor volumes and further revealed the presence of reactive TSPO-expressing glioma-associated microglia/macrophages (GAMMs) in the TME. Conclusion: We confirm the efficiency of [(18)F]FET-PET for monitoring TMZ-treatment response and demonstrate that in vivo TSPO-PET performed with [(18)F]DPA-714 can be used to identify specific reactive areas of myeloid cell infiltration in the TME.